Thinning cycles as the key factor to improve stand productivity in alder plantations - Seyed Mohammad Hojjati; Mahya Tafazoli; Mahshad Ghanizadeh; Mohammad Reza Pourmajidian (Annals of Silvicultural Research)
Considering the high demand for wood and other forest ecosystem services, planning and managing forest plantations to mitigate and answer these increasing issues is necessary. Thinning is one of the most common managing practices for manipulating the growth of planted trees. However, studies about the impact of the thinning-cycle on stand and soil properties are rare for Alnus subcordata C.A.Mey. in Hyrcanian Forests. The aim of this study was to investigate the effect of thinning-cycles on stand and soil properties in the Alnus subcordata plantation in the Hyrcanian Forests, Northern Iran. Three neighboring alder plantations were selected with different thinning treatment cycles: the one-time thinning-cycle (T1, thinned in 2007), three-time thinning-cycle (T3, thinned in 2005, 2010, and 2015), and no thinning as the control (C). In each plantation, 15 plots (20×20 m) were systematic-randomly established (75×50 m grid). In each plot, the characteristics of trees (diameter at breast height (DBH) and total height) and total percentage of vegetation cover were recorded. Soil physiochemical properties were studied by taking samples (0-10 cm) from each plot. The highest value of DBH, total height, tree volume, and basal area and the lowest amount of the total height to DBH ratio were observed in T3. The highest levels of vegetation diversity, evenness, and richness indices were obtained in T3. Soil moisture was significantly higher in the control. The soil pH, electrical conductivity, nitrogen, and potassium were significantly higher in T3. According to the principal component analysis, there was no difference between T1 and control. For this reason, T3 was a more beneficial treatment. Our findings suggested that in alder plantations, the reduction of above and belowground competition via the three-time thinning-cycle, in addition to the financial benefits, not only improves the quality and quantity of the remaining trees but also has a significant potential to improve soil productivity.